Forage potential of grass species under conditions of low temperature and high altitude - Botrel, Milton de Andrade; Alvim, Maurílio José; Ferreira, Reinaldo de Paula; Xavier, Deise Ferreira (Pesquisa Agropecuaria Brasileira, 2002)
The experiment was conducted at Santo Antônio do Pinhal county on a hilly area of Serra da Mantiqueira located in the Paraíba Valley region, in the São Paulo State, Brazil. The aim of this work was to evaluate forages grasses potential for cold tolerance and soil cover. The experimental design was a randomized block with three replications, and treatments were sixteen forages grasses sown on plots of 5 x 5 m. According to the results obtained, the Hemarthria altissima and Setaria anceps species showed the best attributes for monthly dry matter production, crude protein contents, vegetative soil cover and frost tolerance, so they are indicated for pasture establishment in the hilly area of Serra da Mantiqueira of the Paraíba River Valley.